2010
DOI: 10.1136/gut.2009.203000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin and NSAIDs on risk and survival from colorectal cancer

Abstract: This is the first study to demonstrate a protective effect against CRC associated with the lowest dose of aspirin (75 mg per day) after only 5 years use in the general population. NSAID use prior to CRC diagnosis does not influence survival from the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
192
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(203 citation statements)
references
References 82 publications
9
192
0
2
Order By: Relevance
“…These data support a rational DPT approach for treating OC that embodies a therapy that targets specifically nonproliferating cancer cells in combination with a drug regimen that is operational on cells in the proliferative stage of the disease. Although many studies have looked at the role of NSAIDs in cancer therapy, the majority of these have focused on COX inhibition as a mechanism of action for these drugs (21)(22)(23). Decreased sensitivity to chemotherapy and poor prognostic outcome has been associated with ovarian carcinomas expressing COX-2 (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support a rational DPT approach for treating OC that embodies a therapy that targets specifically nonproliferating cancer cells in combination with a drug regimen that is operational on cells in the proliferative stage of the disease. Although many studies have looked at the role of NSAIDs in cancer therapy, the majority of these have focused on COX inhibition as a mechanism of action for these drugs (21)(22)(23). Decreased sensitivity to chemotherapy and poor prognostic outcome has been associated with ovarian carcinomas expressing COX-2 (24).…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs have been evaluated as therapies in different types of cancer (23,34,35) and have been shown to have a synergistic effect with known chemotherapeutic agents (31)(32)(33)(36)(37)(38). However, none of these studies have looked specifically at NSAIDs effects on nonproliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been demonstrated that an inhibition of COX enzymes by non-steroid antiinflammatory drugs or aspirin can reduce the risk of Wnt/ -catenin dependent colorectal cancers significantly [460]. Furthermore, it was shown that Rp-8-Br-cAMP (Table 1), a small molecule inhibitor of PKA, reduces the translocation of -catenin to the nucleus and reduces the expression of Wnt/ -catenin target genes [461].…”
Section: Cross-talk With Other Pathways: Interconnections Between Infmentioning
confidence: 99%
“…It has been indicated to reduce the risk of cancers, including bladder cancer (1), breast cancer (2), glioma (3), and particularly colorectal cancer (4,5). Although the considerable evidence demonstrating that aspirin prevents cancer progression is compelling, the underlying molecular mechanism remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%